Calorie Counter and Diet Tracker - Rosalina Rosalina; Uci Suraitha Karina Br Sitepu (IT for Society, 2016)
Diet is the amount of food consumed by a person or organization, and the way a healthy diet does not mean reducing food portion only. But the meaning of the diet can be described as a set pattern of our own food. Various ways of healthy diet foods can be developed that is appropriate, then, directly or indirectly, to obtain and provide sufficient energy for our bodies even though we can gain the benefits of the diet is that we run with our weight loss. Many people do not know how to calculate how many calories they consume every day, and sometimes the calories consumed exceed the calories they need per day. This research discusses how people can manage a healthy diet based on daily calorie intake. Here will discuss a wide variety of diets such as weight loss, and diet for people with diabetes, cholesterol, gout, stroke, and hepatitis. This research help user regulating daily caloric intake according to the weight and height and also help user to calculate and keep the absence of excessive caloric intake per day.